Emotions as Psychological Reactions - Zamuner, Edoardo (Mind & Language, 2015)
Abstract Sometimes we speak of behaviours and actions as reactions, just as we speak of physical conditions and mental states as reactions. But what do we mean when we say that emotions are reactions? I answer this question by developing an account of emotions as psychological reactions to presentations or representations of states of affairs. I show that this account may provide a novel conceptual framework for explaining aspects of the intentionality, phenomenology and behavioural manifestation of emotions. I conclude by showing that this account is compatible with the view that emotions can be assessed on grounds of justification and correctness.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTExMS9taWxhLjEyMDcw